Systematic review of myxozoan occurrence in Brazilian fish - Araújo, Rafaela Franco; Oliveira, Marcos Sidney Brito; Carvalho, Abthyllane Amaral; Luz, João Gabriel Rosário; Videira, Marcela Nunes; Feiden, Aldi (Frontiers in Marine Science, 2025)
A systematic review was carried out to document the occurrence of myxozoan parasites in farmed and wild teleost fish in Brazil, considering publications made between 1969 and April 2024. This review followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines, and searches were conducted in the Web of Science, Scopus and Pubmed databases. After applying the criteria, 226 articles were selected, recording 286 taxa of myxozoan parasites, of which the genera Henneguya and Myxobolus are the most described in fish in Brazil. Overall, these studies covered ≈ 3% of the more than 4,900 fish species known in Brazilian waters. All reviewed myxozoan genera showed high specificity for infection sites, except Myxobolus, which was a generalist. In the host-parasite interaction network, fish species of importance to Brazilian fishing activity (Pimelodidae, Serrasalmidae, Cichlidae, Bryconidae and Prochilodontidae) obtained the highest number of associations, being the most researched. Regarding the geographic distribution of studies with myxozoans, the majority (79%) occurred with wild fish, originating from all Brazilian river basins, with the exception of the Uruguay River basin. On the other hand, studies that recorded myxozoans in rearing hosts (21% of studies) occurred mainly in the Paraná River basin.